Exploring organizational readiness for ERP HRM implementation using the McKinsey 7S Framework - Cahayadi, Putri Andy; Faza, Ahmad; Wiratama, Jansen (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2025)
This study explores the readiness of PT Halim Lestari Mandiri (PT HLM) for implementing an ERP HRM system, addressing challenges such as high costs and lengthy deployment times. Using the McKinsey 7S framework, a qualitative approach involving focus group discussions (FGDs) was employed to understand factors affecting organizational performance and effectiveness. Four HRM department employees, selected for their knowledge of ERP and understanding of business processes, contributed to data collection through moderated FGDs. Thematic analysis was employed to analyze the data. Results show that a successful ERP HRM implementation requires a comprehensive strategy, covering organizational structure, strategic planning, shared values, technological integration, leadership, communication, and skill development. PT HLM's readiness and adaptability, along with strategic employee development and shared values, create a strong foundation for successful implementation. Improved technological systems and inclusive leadership support accurate decision-making and efficient operations, while ongoing training ensures employees remain well-prepared. This research underscores the importance of an integrated, multifaceted approach to achieving ERP HRM success. It recommends policymakers develop policies that foster organizational readiness and ongoing skill development to adapt to technological advances. The study adds to existing knowledge by providing a detailed, module-specific readiness assessment and emphasizes the need for flexible structures and continuous training to ensure successful ERP HRM implementation.